Sex-specific perturbations of neuronal development caused by mutations in the autism risk gene DDX3X - Adele Mossa; Lauren Dierdorff; Jeronimo Lukin; Marta Garcia-Forn; Wei Wang; Fatemeh Mamashli; Yeaji Park; Chiara Fiorenzani; Zeynep Akpinar; Janine Kamps; Jörg Tatzelt; Zhuhao Wu; et al. (Nature Communications)
Abstract DDX3X is an X-linked RNA helicase that escapes X chromosome inactivation and is expressed at higher levels in female brains. Mutations in DDX3X are associated with intellectual disability (ID) and autism spectrum disorder (ASD) and are predominantly identified in females (DDX3X syndrome). Using cellular and mouse models, we show that Ddx3x mediates sexual dimorphisms in brain development at a molecular, cellular, and behavioral level. During cortical neuronal development, Ddx3x sustains a female-biased signature of enhanced ribosomal biogenesis and mRNA metabolism. Compared to male neurons, female neurons display larger nucleoli, higher expression of a set of ribosomal proteins, and a higher cytoplasm-to-nucleus ratio of ribosomal RNA. All these sex dimorphisms are obliterated by Ddx3x loss. Ddx3x regulates dendritic arborization complexity in a sex- and dose-dependent manner in both female and male neurons. Ddx3x modulates the development of dendritic spines but only in female neurons. Further, ablating Ddx3x conditionally in forebrain neurons is sufficient to yield sex-specific changes in developmental outcomes and motor function. Together, these findings pose Ddx3x as a mediator of sexual differentiation during neurodevelopment and open new avenues to understand sex differences in health and disease.